Repeated use of request for confirmation in atypical interaction. (2nd October 2016) - Rasmussen, Gitte
ABSTRACT: This study investigates a specific method for making possible the participation of participants with cognitive and communicative impairments in social face-to-face interaction. Non-impaired co-participants design close-ended questions that project who the next speaker is, i.e. the impaired co-participant. The questions also project what kind of response amongst alternatives the impaired co-participant is supposed to produce. Upon answers to these questions, the non-impaired co-participant requests the impaired participant to confirm the answer twice. Using conversation analytic (CA) methods, the study scrutinises what is achieved by requesting a confirmation of the provided answer – repeatedly so. The study argues that the practice may put the (deficit) competence of the participant with impairments in focus if the initial close-ended question works to establish an understanding of a prior action by the participant with impairments.